PEMENTASAN TARI KAKELIK PADA UPACARA PIODALAN DI PURA GEDE PEMAYUN DESA PAKRAMAN BANYUNING KECAMATAN BULELENG KABUPATEN BULELENG (Kajian Bentuk, Fungsi, dan Makna) - NYOMAN SUARDIKA (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2018)
The people of Pakraman Banyuning Village who have long tradition of performing Kakelik Dance every time doing piodalan ceremony give order to Kakelik Dance as an important dance balih-balihan sea as wali / Bali. The formulation of the problem in this research are: (1) How is the Kakelik Dance Performance at Piodalan Ceremony at Pura Gede Pemayun Desa Pakraman Banyuning Buleleng District Buleleng Regency? (2) What is the Function of Kakelik Dance Performance at Piodalan Ceremony at Pura Gede Pemayun Desa Pakraman Banyuning Buleleng District Buleleng Regency? (3) What is the Meaning of Kakelik Dance Performance at Piodalan Ceremony at Pura Gede Pemayun Desa Pakraman Banyuning Buleleng District Buleleng Regency?. The theory used in this research is the theory of functionality, theory of symbols, aesthetic theory and sacred theory provanalah data method used is the method of observation, in-depth interview and document recording. The results of this research are (1) the Japanese form of Kakelik Dance performed on piodalan agung Pura Gede Pemayun Banyuning done from jaban temple or nista mandala temple then to Jaba Tengah or Madya Mandala and so on to Main Mandala or Offal temple where every step of dancer sow yellow rice with Uang Kepeng. Selian sprinkled rice dancers take keris to appoint the couple in Jaba Tengan and Utama Mandala temple which later become trance or unconscious. (2) Kakelik Dance Function a) Purification Function b) Function of Expression of Gratitude and expression fuji gratitude Ida Sang Hyang Widhi Wasa c) Cultural Arts Preservation Function d) Religious Education Function e) Education Function S). (3) The Meaning of Kakelik Dance is: a) The Meaning of Kakelik Dance Philosophy b) Meaning of Learning Attitudes Bhakti c) The Meaning of Social Education Culture d) Social Meaning e) Meaning Aesthetics is reflected in the ceremony is dance, dance and role in Kakelik Dance only in the pull in the temple Gede Pemayun Kelurahan banyuning is also used as a factor of achieving sanctity in a yajna. 6) The Meaning of Sanctity Dance is seen from the form of dance which is still natural and the characterization and masudnya yyang different from other dances that dare not be staged at the ceremony of Piodalan agung in Pura Gede Pemayun.